1996
DOI: 10.1149/1.1837152
|View full text |Cite
|
Sign up to set email alerts
|

Possible Cause of the Memory Effect Observed in Nickel‐Cadmium Secondary Batteries

Abstract: After repeated shallow discharging and overcharging of nickel or cadmium capacity‐limited cells, a working voltage lowering of the discharge curve was observed. The magnitude of the lowering was higher in the nickel capacity‐limited cells. The x‐ray diffraction pattern of the charged‐state normal nickel electrode contained diffraction peaks due only to β‐NiOOH. A charged‐state nickel electrode showing a lowered discharge voltage had diffraction peaks due to γ‐NiOOH, in addition to those due to β‐NiOOH.This may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1997
1997
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Our electrochemical tests showed that α-MnSe/Li cell has better cycle performance in the voltage range from 0.01to 3.0 V than from 0.01 to 2.0 V. These results mean that incomplete charging will reduce the reversible capacity and bring poor cycle performance. This phenomenon is similar to the "memory effect" observed in some other electrode materials for lithiumion batteries, such as orthorhombic LiMnO 2 [21], and in Ni-Cd secondary batteries [22]. However, the intrinsic cause is still unknown.…”
Section: Resultssupporting
confidence: 75%
“…Our electrochemical tests showed that α-MnSe/Li cell has better cycle performance in the voltage range from 0.01to 3.0 V than from 0.01 to 2.0 V. These results mean that incomplete charging will reduce the reversible capacity and bring poor cycle performance. This phenomenon is similar to the "memory effect" observed in some other electrode materials for lithiumion batteries, such as orthorhombic LiMnO 2 [21], and in Ni-Cd secondary batteries [22]. However, the intrinsic cause is still unknown.…”
Section: Resultssupporting
confidence: 75%
“…However, the very flat voltage profile of LiFePO 4 makes it difficult to estimate the SOC with high accuracy. Although memory effect is one of the other factors that significantly affect estimation of the SOC in nickel cadmium batteries [21] and nickel metal hydride batteries [22], the absence of a memory effect has often been regarded as one of the advantages of Li-ion batteries. Surprisingly, Sasaki et al [23] reported recently that LiFePO 4 cathode material does exhibit a memory effect.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a reduced working voltage, i.e., the memory effect, is observed in the discharge curves of rechargeable alkaline batteries using a Ni-electrode, such as nickel-cadmium (Ni-Cd), nickel-metal hydride (Ni-MH, where M is a hydrogen absorbing alloy) and nickel-hydrogen (Ni-H 2 ) batteries when they undergo a repeated shallow discharge followed by a full charge or overcharge for a prolonged period of time. [11][12][13][14][15][16][17][18] The memory effect can be defined as the apparent reduction in cell capacity at a fixed cut-off voltage. 19 Further electrochemical investigation proved that the Ni-Cd battery anode fabricated by the as-prepared nanomaterials had no memory effect.…”
mentioning
confidence: 99%